2017
DOI: 10.1007/s11605-017-3503-1
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Result of Prospective Randomized Multicenter Trial of New Spray-Type Bio-absorbable Adhesion Barrier System (TCD-11091) Against Postoperative Adhesion Formation

Abstract: BackgroundPostoperative adhesions are the major cause of postoperative complications including intestinal obstruction, infertility, and chronic pelvic pain. In order to reduce postoperative adhesions, Terumo Corporation (Tokyo, Japan) has developed an adhesion barrier system (TCD-11091) which is easy to use at the treatment site in various surgical procedures including laparoscopic surgeries. We conducted a prospective randomized single-blind study in patients who underwent laparotomy with ileostomy.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…AdSpray is a bioresorbable hydrogel consisting of N-hydroxysuccinimide-modi ed carboxymethyl dextrin and, when applied to injured tissues using a sprayer, it forms a site-speci c physical barrier [21]. A clinical trial demonstrated that it could reduce the incidence, severity, and extent of adhesions following laparotomy in gastrointestinal surgery [22]. Owing to its spray form, it is easy to use in laparoscopic surgery, and its effectiveness has been reported in a laparoscopic gynecological adhesion model in large animals [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AdSpray is a bioresorbable hydrogel consisting of N-hydroxysuccinimide-modi ed carboxymethyl dextrin and, when applied to injured tissues using a sprayer, it forms a site-speci c physical barrier [21]. A clinical trial demonstrated that it could reduce the incidence, severity, and extent of adhesions following laparotomy in gastrointestinal surgery [22]. Owing to its spray form, it is easy to use in laparoscopic surgery, and its effectiveness has been reported in a laparoscopic gynecological adhesion model in large animals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its spray form, it is easy to use in laparoscopic surgery, and its effectiveness has been reported in a laparoscopic gynecological adhesion model in large animals [23]. To our knowledge, although there is some evidence in the literature about the adhesion prevention effect of AdSpray in gastrointestinal or gynecological surgery [21,22,24], evidence in hepatectomy surgery has yet to be published.…”
Section: Discussionmentioning
confidence: 99%
“…AdSpray is a bioresorbable hydrogel consisting of N-hydroxysuccinimide-modified carboxymethyl dextrin and, when applied to injured tissues using a sprayer, it forms a site-specific physical barrier [21]. A clinical trial demonstrated that it could reduce the incidence, severity, and extent of adhesions following laparotomy in gastrointestinal surgery [22]. Owing to its spray form, it is easy to use in laparoscopic surgery, and its effectiveness has been reported in a laparoscopic gynecological adhesion model in large animals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our institution adopts a purse-string closure technique, which is associated with signi cantly fewer SSIs and better cosmetic outcomes with stoma reversal than those associated with conventional primary closure [19], thus potentially reducing the postoperative wound infection rate even after early stoma closure. Furthermore, applying anti-adhesive materials [20] around the stoma could reduce the technical di culties experienced and further improve the results of early stoma closure.…”
Section: Discussionmentioning
confidence: 99%